Fastball pitching performance only slightly decreases after mobility impediment of the pelvis and trunk—Do (catch-up) compensation strategies come into play? - Leenen, A. J. R.; Trigt, Bart van; Hoozemans, M. J. M.; Veeger, H. E. J. (Frontiers in Sports and Active Living, 2022)
Background: As the pelvis and trunk segments are responsible for more than half of the total kinetic energy generated, impeding optimal energy generation or transfer by or between these segments could provide valuable insight into the roles of the well-known principles used to explain baseball pitching performance, namely the summation of speed principle (also coined as the “kinetic chain”) and the principle of optimal coordination of partial momenta. Aim: The aim of the present study was therefore to explore the effects of experimentally impeding the mobility of and between the pelvis and trunk segments 1) on ball speed and mechanical peak joint power, and 2) on mechanical peak load of the elbow and shoulder joints at maximal external rotation (MER) during fastball pitching. Methods: Eleven elite baseball pitchers (mean age 17.4, SD 2.2 years; mean pitching experience 8.9, SD 3.0 years) of the Royal Netherlands Baseball and Softball Federation participated in this study, which consisted of two conditions in which pitchers were instructed to throw fastballs as fast and accurately as possible. One condition involved impeding the mobility of the core segments to hamper their ability to rotate independently, which consequently should affect the separation time, defined as the time interval between the pelvis and trunk peak angular velocities. The other condition involved unimpeded pitching as. Ball speed, mechanical peak joint power and peak net moment of the elbow and shoulder at MER were compared between conditions using the Generalized Estimating Equations (GEE) analysis with the family-wise error controlled by the Bonferroni-Holm method. Results: In the impeded pitching condition, the estimated mean difference of the separation time was 12.4 milliseconds (95% CI [4.0, 20.7]) and the ball speed was 0.6 mph (95% CI [0.2, 0.9]) lower compared to the unimpeded condition. The differences of the peak joint power and net moments at the shoulder and elbow did not reach statistical significance. Conclusion: In elite youth baseball pitchers, experimentally impeding pelvic and trunk mobility decreases ball speed when pitching fastballs but does not affect peak joint power and mechanical loading of the elbow and shoulder.